2011
DOI: 10.1021/tx200181q
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Expression in Peripheral-Blood Samples of Workers Professionally Exposed to Polycyclic Aromatic Hydrocarbons

Abstract: This study aims to examine global gene expression profiles before and after the work-shift among coke-oven workers (COW). COW work six consecutive days and then take two days off. Two blood and urine samples in each worker were collected before starting to work after two-days off and end-of-shift in the sixth-day work in 2009. Altered gene expressions (ratio of gene expression levels between end-of-shift and pre-shift work) were performed by Human OneArray expression system which probes ∼30,000-transcription e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…We therefore would not expect to see substantial overlap between the genes observed in this study and others conducted with tissues from adult organisms. Nevertheless, calcium binding and immune response were identified as important differentially expressed gene clusters in human macrophage leukemia cells exposed to diverse PAHs in vitro, and metal ion binding and transport was the most significant biological process associated with occupational PAH exposure in peripheral blood of coke-oven workers (Wan et al , 2008; Wu et al , 2011b). Chronic PAH exposure in coke-oven workers has also been associated with altered immunological parameters, including increased TNFα in serum, as well increased markers of lipid peroxidation and oxidative stress (Jeng et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore would not expect to see substantial overlap between the genes observed in this study and others conducted with tissues from adult organisms. Nevertheless, calcium binding and immune response were identified as important differentially expressed gene clusters in human macrophage leukemia cells exposed to diverse PAHs in vitro, and metal ion binding and transport was the most significant biological process associated with occupational PAH exposure in peripheral blood of coke-oven workers (Wan et al , 2008; Wu et al , 2011b). Chronic PAH exposure in coke-oven workers has also been associated with altered immunological parameters, including increased TNFα in serum, as well increased markers of lipid peroxidation and oxidative stress (Jeng et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed experimental method is described elsewhere [ 16 ]. Each cDNA sample from the paired tumor and normal parts of the 17 ECC patients was hybridized; thus, a total of 34 chips were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…DNA adducts have indeed been proven to prospectively indicate lung cancer risks in smokers . Differential gene expression in human peripheral blood cells in vivo , responsive to life style, environmental, or occupational exposures, has been reported in several studies (e.g., refs ). In a previous study among smokers and nonsmokers, we have observed significantly affected expressions of relevant genes such as CYP1B1 (cytochrome P450 1B1) and SOD2 (superoxide dismutase 2) and investigated correlations of gene expression and aromatic DNA-adduct levels.…”
Section: Introductionmentioning
confidence: 96%